Malaise dans la philosophie ? - Gaspard Fontbonne (Revue d’Histoire des Sciences Humaines)
In France, philosophy has significant prestige within the hierarchy of academic disciplines. It has also produced a large number of intellectual “renegades” instrumental in founding new disciplines (sociology, anthropology, psychology, the educational sciences, psychoanalysis). In the late 1960s, psychoanalysis was highly influential in the intellectual field, particularly on philosophers, who often joined its ranks. The empirical research presented in this article was required in order to counter the common-sense explanations given: thus we examine the conditions under which agents initially trained in a speculative discipline such as philosophy came to devote themselves to the practice of psychoanalysis. By scrutinising agents' trajectories, the article also shows the extent to which the different modes of access to this new position depend on the agents' social properties.